BEYOND EXPECTATIONS: A MOTHER'S JOURNEY WITH A CHILD WITH DOWN SYNDROME - Wahyuni, Sri; Januarti, Andini; Amelia, Dara Siska; Fitar, Maia Amelia; Yunita, Harpiza Apri; Levindra, Nadia Viska; Mulyani, Endah; Oktavia, Siski (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This research aims to explore mothers' experiences in caring for children with Down syndrome by focusing on the challenges they face and the strategies used to overcome them. This research uses a qualitative phenomenological research type with an Interpretative Phenomenological Analysis (IPA) approach, with a focus on in-depth interviews involving two mothers who have Down syndrome children. The research results show that there are 4 ultimate themes from both subjects, namely (1) Child behavior, (2) Optimism, (3) Emotional turmoil, and (4) Social support. Social support from family and neighbors, and optimism play an important role in helping mothers to overcome the challenges faced in caring for children with Down syndrome. This research provides valuable insight into the importance of social support and optimism in helping individuals, especially mothers with children with Down syndrome, in facing the challenges of caring for children with Down syndrome.